Exploring Student Engagement in Sustainability Education and Study Abroad - Michael Tarrant (MDPI AG, 2021)
This paper specifically outlines an investigation of the influence of sustainability education and study abroad coursework on levels of a key component of academic success, student engagement. A quasi-experimental design compared pretest and posttest levels of engagement (measured by the Deep Learning Scale) among undergraduate students enrolled in four types of courses). Data were analyzed using a repeated measures MANOVA and supported two significant 2-way interactions (Sustainability * Time and Study Abroad * Time) suggesting that student engagement (Deep Learning) is more likely to increase with sustainability (than non-sustainability) courses and with study abroad (than non-study abroad/campus courses). Findings provide empirical support for university initiatives that seek to incorporate sustainability coursework and study abroad opportunities into the undergraduate curriculum as means to enhance students’ overall engagement and academic success. The paper provides insights into where sustainability education and study abroad courses have broad potential to promote engagement and, as such, should be considered part of the general learning requirement of university education. In terms of study limitations, the sample is drawn from one university and self-selection bias is possible for students choosing to enroll in study abroad and sustainability-focused courses.